Mexico : Financial Sector Assessment Program Update; Technical Note; Derivatives Market; Overview and Potential Vulnerabilities. (IMF Staff Country Reports; Country Report, 2007)
This technical note provides an overview of Mexico's derivatives markets, and describes concisely the derivatives regulatory framework and risk management practices in financial institutions active in these markets. The most important derivatives market in Mexico is the over-the-counter (OTC) derivatives market, which is fully integrated with the global derivatives market. The origin of the OTC derivatives market can be traced back to the 1994 Mexican crisis that forced Mexico to abandon its fixed exchange rate regime.